Latin American consensus on psoriasis severity classification - Angela María Londoño-García; Juan Raúl Castro-Ayarza; Manuel Darío Franco Franco; Cesar Fernando González Ardila; Gabriel Magariños; Enrique Salvador Rivas Zaldívar; Susan Martínez; Linda Ibatá; Julieth Carolina Castillo; Paola Jimena Cárdenas Rojas; Evelyn Giuliana Castro Vargas; Claudia Romina Contreras; et al. (Anais Brasileiros de Dermatologia)
Abstract: Background: There are different classifications of psoriasis based on its clinical presentation, impact on quality of life, requirements for specific treatments, and other patientor physicianreported outcomes. However, the lack of unified definitions has led to the severity of the disease being underestimated. Standardizing the classification of psoriasis will promote a better approach to the disease and facilitate care by professionals. Objective: To present a consensus of experts in Latin America regarding the classification of psoriasis severity, based on the best available evidence and applicable to current medical practice in the region. Methods: An independent methodological team, together with a group of clinical dermatologists representatives from different Latin American countries, developed a consensus witha modified Delphi methodology based on a systematic review of the literature. This consensus includes the classification of psoriasis, tools to define the severity of psoriasis, and other considerations in evaluating patients with psoriasis. Results: Fifteen statements were formulated aimed at classifying the severity of cutaneous psoriasis and other forms of the disease, as well as tools to assess and define the severityof psoriasis and therapy considerations. Additionally, the consensus addresses implementation considerations. Conclusion: The results of this consensus constitute a solid basis for a standard classification terminology for the varied clinical forms of psoriasis and their therapeutic implications. The importance of maintaining a personalized therapeutic approach, adjusted to each country’s available resources and administrative realities, is highlighted.